“Soldiers of the System”: Maternity Care in Russia Between Bureaucratic Instructions and the Epidemiological Risks of COVID-19 - Ozhiganova, Anna (Frontiers in Sociology, 2021)
Preventive measures taken by the Russian maternity care system in response to the COVID-19 pandemic are very tough. Supporting persons (doulas and partners) are being completely excluded from the maternity hospitals. Pregnant women and newborns are distributed in different types of hospitals according to their epidemiological status (confirmed, suspected, contact, or “clear”). Severe infection control measures are introduced for women with confirmed or suspected COVID-19: separation from newborns and weeks of hospital quarantine. How do obstetricians and other perinatal specialists perceive these measures? What strategies do they choose and what new practices are being created? The study is based on interviews conducted between March and August 2020 with obstetricians-gynecologists, midwives, perinatal psychologistsdoulas, and women who gave birth during the pandemic and is focused on their subjective interpretations of COVID-related changes in maternal care. My data indicate that this pandemic with its high risks and uncertainties reveals multiple ethical and organizational conflicts among bureaucratic, managerial and professional logics in Russian health care in which mistrust has played an important role.